KOMUNIKASI ORANGTUA DENGAN GURU BK MENGENAI DISIPLIN ANAK BELAJAR DI RUMAH - Muhammad Rizan Fadhilah; Khairuddin Tambusai (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This research was conducted at Madrasah Aliyah Laboratorium UIN Sumatera Utara Medan (MAL UIN SU Medan). The objectives are 1) To describe how learning discipline at home, and 2) Describing how parents communicate with counseling teachers about learning discipline at home. The method used in this research is a qualitative method, research data collection is done by interview, observation, and documentation. The steps taken in analyzing data are by reducing data, presenting data, drawing conclusions or veirification. The findings of this study indicate that: the discipline of learning at home students is still very lacking both from internal factors and external factors. The cause of internal factors causing students to behave lazily studying at home is the lack of student understanding of learning materials. External factors causing students to behave lazily studying at home, namely limited learning facilities in the form of inadequate cellphones and unstable internet network signals and the presence of peers who invite to do assignments at home.